Photovoltaic cell modeling for maximum power point tracking using MATLAB/Simulink to improve the conversion efficiency - Das, Narottam; Wongsodihardjo, Hendy; Islam, Syed (IEEE, 2013)
This paper focuses on the behavior of maximum power point tracking (MPPT) on photovoltaic (PV) cell systems using MATLAB/Simulink software. The PV cells can offer better simulation results when a double-exponential type, i.e., double-diode model is used. The reason, it is more accurate with the real testing condition even though the efficiency is a bit less. This confirms that theoretical single-diode model still require more improvements. In addition, multijunction solar cell also investigated to obtain its maximum performance compared with the conventional silicon PV cell. The obtained results show that the tandem (or multijunction) cell can provide almost 3-times maximum power compared to the conventional PV cell. Therefore, the multijunction/ tandem PV cells can produce higher power throughout the sunny day due to the higher MPPT capacity. Furthermore, perturb and observe method seems to be very useful because of its simplicity despite the unresolved algorithm for different methods, such as constant voltage tracking technique.